Fatigue Properties of Ti Alloys with an Ultrafine Grained Structure: Challenges and Achievements - Irina Petrovna Semenova; Yulia Mikhailovna Modina; Andrey Gennadievich Stotskiy; Alexander Vadimovich Polyakov; Mikhail Vladimirovich Pesin (Metals, 2022)
Ultrafine-grained (UFG) structure formation in Ti alloys, by severe plastic deformation (SPD) processing and enhancement of their mechanical properties, including fatigue properties, has been demonstrated in numerous studies in the past 20 years. The present overview analyzes the fatigue properties achieved to date in Ti alloys subjected to SPD. Such aspects are examined as the effect of a UFG structure on the fatigue behavior of commercially pure (CP) Ti, two-phase Ti alloys, using the popular Ti-6Al-4V alloy as an example, as well as on the kinetics and mechanisms of fatigue failure. The prospects and problems of the practical application of UFG Ti materials in medicine and aircraft engine construction are discussed.